Maternal consumption of a high-fat diet modulates the inflammatory response in their offspring, mediated by the M1 muscarinic receptor - Costa, Suleyma Oliveira; Chaves, Wenicios Ferreira; Lopes, Priscilla Karla Fernandes; Silva, Iracema M.; Burguer, Beatriz; Ignácio-Souza, Leticia M.; Torsoni, Adriana Souza; Milanski, Marciane; Rodrigues, Hosana Gomes; Desai, Mina; Ross, Michael Glenn; Torsoni, Marcio Alberto (Frontiers in Immunology, 2023)
High-fat diet (HFD) consumption is associated with metabolic disorders and diseases. Both pre-pregnancy and maternal obesity can have long-term consequences on offspring health. Furthermore, consuming an HFD significantly increases the risk of obesity and metabolic disorders. However, a phenomenon known as the obesity paradox suggests that obesity may confer a protective effect on mortality outcomes in sepsis. In sepsis, activation of the cholinergic anti-inflammatory pathway (CAP) mitigateS systemic inflammation. We employed a metabolic programming model to explore the relationship between maternal HFD consumption and offspring response to sepsis. We fed female mice either a standard diet (SC) or an HFD during the pre-pregnancy, pregnancy, and lactation periods. Subsequently, we evaluated 28-day-old male offspring. Notably, we discovered that offspring from HFD-fed dams (HFD-O) exhibited a higher survival rate compared with offspring from SC-fed dams (SC-O). Inhibition of m1 muscarinic acetylcholine receptor (m1mAChR) in the hypothalamus abolished this protection. The expression of m1mAChR in the hypothalamus was higher in HFD-O at different ages, peaking on day 28. Treatment with an m1mAChR agonist modulateS the inflammatory response in peripheral tissues. CAP activation was greater in the liver of HFD-O following agonist treatment. Lipopolysaccharide (LPS) challenge failed to induce a more inflammatory state in HFD-O, in contrast to SC-O, and agonist treatment had no additional effect. Analysis of spleen immune cells revealed a distinct phenotype in HFD-O, characterized by elevated levels of CD4 + lymphocytes rather than CD8 + lymphocytes. Moreover, basal Il17 mRNA levels were lower while Il22 mRNA levels were higher in HFD-O, and we observed the same pattern after LPS challenge. Further examination of myeloid cells isolated from bone marrow and allowed to differentiate showed that HFD-O macrophages displayed an anti-inflammatory phenotype. Additionally, treatment with the m1mAChR agonist contributed to reducing inflammatory marker levels in both groups. In summary, our findings demonstrate that HFD-O are protected against LPS-induced sepsis, and this protection is mediated by the central m1mAChR. Moreover, the inflammatory response in the liver, spleen, and bone marrow-differentiated macrophages is diminished. However, more analysis is necessary to elucidate the specific mechanisms by which m1mAChR modulates the immune response during sepsis.